Pengaruh ATK terhadap Produktivitas Kerja pada Balai Penyuluhan Pertanian dan Kehutanan (BPPK) Peureulak Aceh Timur - Fitrianti; M Djamil HS (Yayasan Kawanad, 2022)
This research aims to explore the influence of Office Stationery (ATK) on work productivity at the Peureulak Agricultural and Forestry Extension Center (BPPK), East Aceh. Quantitative research methods are used with a survey approach, involving active employees in extension activities. The results show that the quality of stationery, efficiency of use, and comfort of the work environment have a positive impact on employee perceptions of productivity. Factors such as creativity, innovation, cost savings and technology integration have also proven relevant. In conclusion, management that pays attention to the selection and effective use of ATK can improve operational efficiency and employee welfare. Further implications emphasize the need for special attention to the role of ATK in increasing productivity in various organizational sectors